The challenges faced by women-owned small businesses in Lepelle-Nkumpi Local Municipality, Limpopo Province, South Africa - Makola, Lerato Madilo (My University, 2022)
In today‟s post-modern era, the role of women-owned small businesses in economic development is inevitable. Women are willing to act in business and contribute to the nation‟s growth. However, most women in small businesses face a wide variety of challenges both in starting and in growing their business ventures. Some of the challenges relate to lack of skills and an environment that is not favourable to women small business owners. Thus, a study was conducted in Lepelle-Nkumpi local municipality in Limpopo Province. The aim of the study was to investigate the challenges faced by women-owned small businesses in the Lepelle-Nkumpi local municipality, Limpopo Province of South Africa. The study used a qualitative research method to collect data. Fifteen (15) individuals participated in the study; twelve (12) of the participants were women who owned small businesses in the municipality and three (3) of the participants were officials working in the LED unit. Participants in the study were chosen purposively because of the knowledge that they possessed. Semistructured interviews were used in the qualitative study to collect data. The study discovered that some of the challenges included lack of skills and training, lack of access to finance, lack of marketing strategies and inadequate resources. Thus, the study recommended that the municipality should provide need-based training for small business owners.
Thesis (MBA.) -- University of Limpopo, 2022
Keywords: Women-owned small businesses; Need-based training; Small businesses; Economic development -- South Africa -- Limpopo; Small business -- South Africa -- Limpopo; Women-owned business enterprises